2001
DOI: 10.1097/00004714-200110000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Pilot Study of the Ampakine CX516 Added to Clozapine in Schizophrenia

Abstract: CX516, a positive modulator of the glutamatergic alpha-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptor, improves performance in tasks requiring learning and memory in animals. CX516 was added to clozapine in 4-week, placebo-controlled, dose-finding (N = 6) and fixed-dose (N = 13) trials. CX516 was tolerated well and was associated with moderate to large, between-group effect sizes compared with placebo, representing improvement in measures of attention and memory. These preliminary results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(122 citation statements)
references
References 13 publications
2
112
1
5
Order By: Relevance
“…In this study, significant improvements in memory and attention were observed despite lack of symptomatic improvement. 118 CX-516 has also been studied as monotherapy, with no clear beneficial effects. 119 Although downregulation of AMPA receptors is less with AMPAkines than with direct agonists, there is some concern that downregulation may nonetheless occur and may limit long-term treatment strategies.…”
Section: Other Ionotropic Targetsmentioning
confidence: 99%
“…In this study, significant improvements in memory and attention were observed despite lack of symptomatic improvement. 118 CX-516 has also been studied as monotherapy, with no clear beneficial effects. 119 Although downregulation of AMPA receptors is less with AMPAkines than with direct agonists, there is some concern that downregulation may nonetheless occur and may limit long-term treatment strategies.…”
Section: Other Ionotropic Targetsmentioning
confidence: 99%
“…Furthermore, preliminary human studies have suggested that ampakines may have a positive memory encoding effect with respect to visual associations, recognition of odors, acquisition of a visuospatial maze, location and identity of playing cards (Ingvar et al 1997), and enhances delayed recall in older individuals (Lynch et al 1997). Finally, in very preliminary studies of schizophrenic patients, CX516 was added to clozapine in 4-week, placebo-controlled, dose-finding and fixed-dose trials and was suggested to exert beneficial effects in measures of attention and memory (Goff et al 2001). An investigation of CNS-penetrant AMPA modulating agents in the treatment of depression is clearly warranted.…”
Section: The Glutamatergic System As a Target For Novel Antidepressanmentioning
confidence: 99%
“…One was a double-blind placebo-controlled trial in which CX516 was added to clozapine treatment for 4 weeks ((19 patients in total: 12 were allocated to CX516 treatment and seven to the placebo treatment group) Goff et al, 2001). The ampakine group showed moderate to large improvements compared to the placebo group on attention and memory performance and showed a reduction of negative symptoms.…”
Section: Introductionmentioning
confidence: 99%